Characteristics of Magical Realism in Fantastic Beasts and Where to Find Them Film By J.K. Rowling - Andi Febriana Tamrin; Onna Onna; Basri Basri (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. This research analyzes the characteristics of magical realism in the film Fantastic Beasts and Where to Find Them by J.K. Rowling. This study uses the magical realism theory of Wendy B. Faris. This research aimed to determine the characteristics of magical realism contained in the Fantastic Beasts and Where to Find Them film.  This research method uses the documentation technique. The data source of this research is the film Fantastic Beasts and Where to Find Them by J.K. Rowling, which was released in 2016 and with duration 2 hours 3 minutes. The main theory in this study uses the magical realism theory of Wendy B. Faris, which is contained in the book Ordinary Enchantments Magical Realism and the Remystification of Narrative (2004). The results of this research indicate that there are five characteristics of magical realism in Fantastic Beasts and Where to Find Them, namely the irreducible element, unsettling doubt, merging realism, disruption of space, and disruption of identity. Keywords: Magical Realism, Characteristics of Magical Realism, FIlm